Cannabinoids for spasticity due to multiple sclerosis or paraplegia: A systematic review and meta-analysis of randomized clinical trials - da Rovare, Victoria P. [UNESP]; Magalhães, Gabriel P.A. [UNESP]; Jardini, Guilherme D.A. [UNESP]; Beraldo, Matheus L. [UNESP]; Gameiro, Mariel O. [UNESP]; Agarwal, Arnav; Luvizutto, Gustavo José [UNESP]; Paula-Ramos, Lucas [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; de Oliveira, Luciane Dias [UNESP]; Bazan, Rodrigo [UNESP]; El Dib, Regina [UNESP] (Elsevier, 2017)
Objectives Spasticity remains highly prevalent in patients with spinal cord injury and multiple sclerosis. To summarize the effects of cannabinoids compared with usual care, placebo for spasticity due to multiple sclerosis (MS) or paraplegia. Methods Searches of MEDLINE, EMBASE, CENTRAL and LILACS to March 2017 were performed to identify randomized controlled trials. The primary outcomes were spasticity and spasm frequency. The criteria were any patient with MS and spasticity affecting upper or lower limbs or both, and that had a confirmed diagnosis of MS based on validated criteria, or however defined by the authors of the included studies. Results 16 trials including 2597 patients were eligible. Moderate-certainty evidence suggested a non-statistically significant decrease in spasticity (standardized mean difference (SMD) 0.36 [confidential interval (CI) 95% −0.17 to 0.88; p = 0.18; I2 = 88%]), and spasm frequency (SMD 0.04 [CI 95% −0.15 to 0.22]). There was an increase in adverse events such as dizziness (risk ratio (RR) 3.45 [CI 95% 2.71–4.4; p = 0.20; I2 = 23%]), somnolence (RR 2.9 [CI 95% 1.98–4.23; p = 0.77; I2 = 0%]), and nausea (RR 2.25 [CI 95% 1.62–3.13; p = 0.83; I2 = 0%]). Conclusions There is moderate certainty evidence regarding the impact of cannabinoids in spasticity (average 0.36 more spasticity; 0.17 fewer to 0.88 more) due to multiple sclerosis or paraplegia, and in adverse events such as dizziness (419 more dizziness/1000 over 19 weeks), somnolence (127 more somnolence/1000 over 19 weeks), and nausea (125 more somnolence/1000 over 19 weeks).
Keywords: Cannabinoids; Multiple sclerosis; Paraplegia; Spasticity